United Kingdom Veterinarians’ Perceptions of Clients’ Internet Use and the Perceived Impact on the Client–Vet Relationship - Kogan, Lori R.; Oxley, James A.; Hellyer, Peter; Schoenfeld-Tacher, Regina (Frontiers in Veterinary Science, 2017)
The internet is a commonly used resource for accessing health information. Despite the internet’s popularity in the human health field, little is known about the internet’s impact on veterinarians, their clients and the veterinarian-client relationship. The aim of this study was to investigate the perception of veterinarians from the United Kingdom of clients’ use of the internet and the perceived impact on pet health and the veterinarian-client relationship. A survey was distributed between January 4th and March 3rd, 2017 via an online link. In total, 100 veterinarians completed the survey. This study found that most UK veterinarians feel their clients access the internet to find pet health information, yet often do not understand what they read online. Importantly, 40% of veterinarians stated that the internet has a negative impact on companion animal health. This small scale study found mixed opinions regarding veterinarians’ perceptions of their clients’ use of the internet and the potential impact it has on the client-veterinarian relationship, and research on clients’ actual use of the internet and their associated perceptions is a next logical step.